Pengaruh Penambahan Soda Potash Pada Air Sebagai Campuran Beton - Eritson Prasetiawan; Frans Phengkarsa; Desi Sandy (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
The purpose of adding soda potash to water for the mixture in this test is one way to determine the effect of soda potash on the concrete mixture. Jeneberang River is where coarse aggregate and fine aggregate are taken. One of the chemical stores, Makassar City, South Sulawesi is where potash soda is obtained. SNI 7656 – 2012 is the method used in Mix Design. 7, 21 and 28 days are the time for concrete compressive strength testing and the Compression Testing Machine tool is a tool used to determine the maximum concrete strength at the time of receiving compressive load. At a concrete age of 28 days variations of 0% were obtained (24,889 MPa), 7.5% (25,643 MPa), 10% (24,983 Mpa), and 12.5% (23,946 Mpa). Based on the test results, the average tensile strength of concrete was obtained for variations of 0% (2.286 MPa), 7.5% (2.475 Mpa), 10% (2.357 Mpa), and 12.5% (2.121 MPa). The average bending strength of concrete at variations of 0%, 7.5%, 10%, and 12.5% is 2.569 MPa, 2.795 MPa, 2.594 Mpa and 2.418 MPa. For the hsil modulus of elasticity test, test results were obtained at variations of 0% (23263.149 Mpa), 7.5% (23419.95Mpa), 10% (23391.058Mpa), 12.5% (23254.858Mpa).